Tunable Push-Pull Interactions in 5-Nitrosopyrimidines - Procházková, Eliška; Čechová, Lucie; Tarábek, Ján; Janeba, Zlatko; Dračínský, Martin (The Journal of organic chemistry, 2016)
The effect of push-pull interactions in a series of variously substituted 5-nitrosopyrimidines on the strength of intramolecular hydrogen bonds, the height of rotational barriers around formally single bonds, UV-vis spectra and electrochemical behavior is explored. Intramolecular charge transfer (ICT) leads to a shift of electron density from electron-donating substituents, which is readily observable by NMR spectroscopy. The 5-nitroso group is able to form strong intramolecular hydrogen bonds with neighboring amino substituents. As a result, two rotamers with reversed orientation of the 5-nitroso group are observed for compounds with two different hydrogen-bond donors in neighboring positions. The barriers of interconversion between the two rotamers are strongly influenced by ICT, whereas the ratio of such rotamers depends primarily on the character of the hydrogen-bond donors. The ICT also significantly affects the position of UV-vis absorption maxima, which can be tuned in a broad range of 100 nm by the selection of appropriate substituents. Finally, ICT influences oxidation potential of the 5-nitrosopyrimidines and the stability of the resulting nitroso radical cations, the structures of which are determined by EPR spectroscopy.